Ironist liberalism in thoughts Richard Rorty - Farha, Mohammad; Mallah, Heba (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This paper deals the term of ironist liberalism in its pragmatic nature in Richard Rorty philosophy, Based from the definition of the nature of the relationship between liberalism and ironist, In rethinking post modernism in liberty and their positions on the philosophical and political level, By standing on modern perception of religion Rorty,Which is considered the most important leap forward Rorty in our contemporary world, With its distinctive effect in his new pragmatism philosophy, That affected with the philosophy of John Dewey, Which has consistently referred to the overall philosophical and religious ideas to the our real world, and try to call our utopian ideas and attracting its usefulness our real world, Based on the policy of caring for the suffering of human beings and their pains. Beyond all traditional liberal and religious theories. This research also aims at clarifying the meaning of social utopian at Rorty, and its role and embodiment by simulating the poetic subject in American society, and transition from final worlds to the infinite worlds, trying to shed light on this political- philosophical transgression, Which Rorty introduced to new pragmatic philosophy, so that we can reach what is known as dialogue on the threshold of my community of talks. Based on the balance and social solidarity between the ego and the other.